Lizards paid a greater opportunity cost to thermoregulate in a less heterogeneous environment. (21st November 2016) - Basson, Christine H.; Levy, Ofir; Angilletta, Michael J.; Clusella‐Trullas, Susana
Summary: The theory of thermoregulation has developed slowly, hampering efforts to predict how individuals can buffer climate change through behaviour. Mixed results of field and laboratory experiments underscore the need to test hypotheses about thermoregulation explicitly, while measuring costs and benefits in different thermal landscapes. We simulated body temperature and energy expenditure of a virtual lizard that either thermoregulates optimally or thermoconforms in a landscape of either low or high quality (one or four basking sites, respectively). We then compare the predicted values in each landscape with the observed values for real lizards in experimental arenas. Lizards thermoregulated more accurately in the high‐quality landscape than they did on the low‐quality landscape, albeit only slightly so, but spent similar amounts of energy in these landscapes. Basking, rather than shuttling between heat sources, accounted for the majority of the energy consumed in both landscapes. These results did not support the predictions of our model. In the low‐quality landscape, real lizards thermoregulated intensely despite the potential to save energy by thermoconforming. In the high‐quality landscape, lizards moved more than expected, suggesting that lizards explored their surroundings despite being able to thermoregulate without doing so. Our results suggest that non‐energetic benefits drive thermoregulatory behaviour in costly environments, despite the missed opportunities arising from thermoregulation. We propose that energetic costs associated with thermoregulatory movement will become substantial in homogeneous environments such as flat plains and dense forests. The theory of thermoregulation should incorporate these aspects if biologists wish to predict responses of ectotherms to changing climates and habitats. A lay summary is available for this article. Abstract : Lay Summary